BEST PERFORMING CRYPTO ASSETS 2020-2023 - Reksha Laksana; Fauziyah, Elyatul (Penelitian dan Pengembangan Ilmu, 2024)
This study aims to analyze the performance of crypto assets in the period 2020 to 2023. This research is a quantitative descriptive research, with the sampling method using saturated sampling. During the observation period, 1440 monthly closing data were collected from 30 crypto assets with the largest market capitalization in the world that became the population. The results show that crypto assets are highly volatile and unpredictable, high-risk assets such as Fantom (FTM) and Thorchain (RUNE) tend to offer higher returns, but with significant fluctuations in value. Meanwhile, lower-risk assets like Leo Token (LEO) offer greater stability but with more limited growth potential. These findings can be taken into consideration for investors in making decisions regarding their investment in crypto assets.